KINETIKA PROSES AOPs UNTUK PENGHILANGAN WARNA AIR LIMBAH PRODUKSI BATIK - Nugroho, Rudi; Mahmud, Ikbal (Center for Environmental Technology, 2005)
An experiment of Advanced Oxydation Processes (AOPs) was conducted in semi-pilot scale using ozon and hydrogen peroxide. The reaction of ozon and hydrogen peroxideÃ‚Â produce an active hydroxil which can crack a long-chain organic compounds such as azo dyes. A wastewater contains colour substances coming from batik industries in Jababeka was treated by AOPs. The reaction rate was affected by ozon concentration supplied to the wastewater. The more ozon concentration, the colour removal became faster.The colour removal using AOPs could be illustrated by first-order chemical reaction equation.The constant of reaction was calculated from experiment as high as 0,38 per hour.The cost for treating the wastewater using AOPs wasÃ‚Â Rp.3.656,- for one cubic meter of wastewater.Ã‚Â Key words: Ã‚Â AOPs, Colour Removal, Hydrogen Peroxide, Ozon,